Pharmacognostical Studies on Root of Fagonia schweinfurthii Hadidi - Rathore, Manoj K. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTFagonia schweinfurthii (family zygophyllaceae) is a plant of desert region. It is commonly known as dhamasa and dhamasia. It is small, spiny, erect, undershrubs, more and less grandullar; branchess slander, terete, triage, glabrous. Leaves opposite, 1-3 foliate; petioles very variable in length, from 3 - 30 mm long, deeply striate, very slender; stipules 2 pairs of sharp slender thorns, sometimes exceeding 12 mm in length; leaflets linear, acute, sessile or with very short petiolules. Traditionally, the plant has been used to cure a number of ailments by the people living in desert region such as skin eruptions, in heal sores, skin diseases, anti-pyretic, in pain relief, ear infection, venereal diseases, etc. many other diseases. The present paper deals with comprehensive pharmacognostical studies on root part of this plant, including macroscopical analysis, preliminary examination of root powder, florescence analysis. This will help in the identification of powder drug prior using in any herbal formulations.